Association Between Comitant Strabismus and Refractive Error in Children Attending a Tertiary Eye Care Center - Tripathi, Bishal Mani; Bhusal, Usha; Rayamajhi, Jharana; Pal, Suraj; Pangeni, Rakshya; Sapkota, Anjana (Journal of Bharatpur Hospital, 2026)
Background Comitant strabismus is a common ocular disorder in childhood and is frequently associated with refractive errors, which may lead to amblyopia and long-term visual impairment if not detected early. While this association has been well documented in high-income countries, evidence from low- and middle-income settings such as Nepal remains limited. Methods A hospital-based cross-sectional study was conducted from September 2024 to September 2025 among children aged 4-16 years diagnosed with comitant strabismus at a tertiary eye care center. Ethical approval was obtained from the Institutional Review Committee, and written informed consent was obtained from parents or guardians before participation. Comprehensive ophthalmic evaluation was performed, including cycloplegic refraction using streak retinoscopy. Differences in spherical equivalent among strabismus types were analyzed using the Kruskal–Wallis test with Dwass-Steel-Critchlow-Fligner post hoc comparisons. Results A total of 243 children were included. Refractive error was present in 70% of cases. Esotropia showed the highest proportion of refractive error (83.7%), with hyperopia accounting for 63% of these cases. Exotropia was more frequently associated with myopia and emmetropia. A significant difference in spherical equivalent was observed among esotropia, exotropia, and hypertropia (χ² = 54.5, df = 2, p < 0.001, ε² = 0.225). Post hoc analysis demonstrated significantly more hyperopic refractive status in esotropia compared to exotropia (p < 0.001). Conclusions Refractive error is highly prevalent among children with comitant strabismus, with hyperopia predominantly associated with esotropia, highlighting the importance of routine cycloplegic refraction in pediatric strabismus evaluation.